Lee, Peter The Great; Marshall, Peter The Great - Micciche, Pasquale (Teaching History: A Journal of Methods, 1997)
Two very similar books with the exact same title designed to augment the typical textbook survey of one of Russia's most turbulent, complex, and historic periods-that of Peter the Great. Both works are authored or edited by English scholars. S. J. Lee's volume on Peter is part of the "Lancaster Pamphlets" series that includes more than 40 titles on major topics in European history. William Marshall's volume, nearly twice the length of Lee's, is part of the "Seminar Studies in History" series, a series of approximately 75 titles on British and world history and edited by R. Lockyer, Emeritus Reader in History at the University of London. While both books share several basic features and purposes, they also have a few significant differences as well.